Monounsaturated fatty acid antagonizes saturated fatty acid-induced cardiomyopathy via improving membrane fatty acid composition and endoplasmic reticulum stress. (14th October 2021) - Yamamoto, T Y; Endo, J E; Shinmura, K S; Sano, M S; Fukuda, K F
Abstract: Background: Obesity-induced lipotoxicity causes cardiac dysfunction in our modern lifestyle. Previously, we have shown that an increase in cardiomyocyte membrane saturated fatty acid (SFA)/ monounsaturated FA (MUFA) ratio mediates endoplasmic reticulum (ER) stress, which was implicated in the pathogenesis of SFA-induced cardiomyopathy. Furthermore, SFA supressed Sirt1/ stearoyl-CoA desaturase-1 (SCD1, converting enzyme from SFA to MUFA) signaling, which further worsened the membrane SFA/MUFA ratio. Purpose: To evaluate the effectiveness of targeting membrane fatty acid composition by MUFA. Methods and results: In wild-type mice, 16-weeks SFA-rich high lard diet feeding (HLD) caused activation of PPARα signaling and the accumulation of toxic lipid intermediates (diacylglycerol and ceramide) in the heart to the same extent as a MUFA-rich high olive oil diet feeding (HOD). However, only the HLD impaired Sirt1 activity, SCD1 expression, diastolic function (increased left ventricular end-diastolic pressure (LVEDP) and end-diastolic pressure-volume relationship (EDPVR)), and cardiac remodeling (hypertrophy and fibrosis). Lipidome analysis showed that HLD-induced diastolic dysfunction coincided with an increase in membrane SFA/MUFA ratio and ER stress induction. 8-weeks HOD after 8-weeks HLD (HOD switch) showed the same degree of obesity and PPARα activation with 16-weeks HLD. By contrast, HOD switched heart were less severe Sirt1/SCD1 signaling dysregulation, increased in membrane SFA/MUFA ratio, ER stress, and cardiomyopathy (hypertrophy, fibrosis, and diastolic dysfunction) compared to 16-weeks HLD. Moreover, in cardiomyocyte-specific Sirt1 knockout mice, HOD switched heart also showed less severe increase in membrane SFA/MUFA ratio, ER stress, and cardiomyopathy compared to 16-weeks HLD although decreased SCD1 expression was not changed. Conclusions: We demonstrated that MUFA-rich diet counteracted SFA-induced Sirt1/SCD1 signaling dysregulation and prevented SFA-induced increase in membrane SFA/MUFA ratio. Hence, MUFA-rich diet antagonized SFA-induced ER stress and cardiomyopathy even if Sirt1 deactivated heart (e.g., aged heart). Targeting the cardiomyocyte membrane SFA/MUFA ratio by MUFA might have a new therapeutic potential for SFA-induced cardiomyopathy. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): JSPS KAKENHI